2007
DOI: 10.1016/j.psyneuen.2006.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Hypercortisolemic depression is associated with the metabolic syndrome in late-life

Abstract: SUMMARYIntroduction-Depression has been hypothesized to be associated with metabolic abnormalities which increase the risk of cardiovascular disease and diabetes. Such a link could be due to increased HPA-axis activity. This study investigates the cross-sectional relationship between depression, urinary cortisol and metabolic syndrome in an older population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
168
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 195 publications
(189 citation statements)
references
References 46 publications
13
168
0
6
Order By: Relevance
“…Although this is indeed a potentially interesting mechanism, our data do not provide much evidence for a large effect of hyperinsulinemia. In our study among 867 older persons (Vogelzangs et al, 2007), we showed that hypercortisolemic depression was associated with the metabolic syndrome in an older population. Although we found a weak association between 24-h urinary cortisol and serum glucose in the total sample (adjusted β = 0.08, p = .02), among depressed persons (N=179) cortisol appeared to be associated more strongly with the obesity-related components of the metabolic syndrome such as waist circumference, triglycerides, and high density lipoprotein cholesterol than with serum glucose.…”
mentioning
confidence: 50%
“…Although this is indeed a potentially interesting mechanism, our data do not provide much evidence for a large effect of hyperinsulinemia. In our study among 867 older persons (Vogelzangs et al, 2007), we showed that hypercortisolemic depression was associated with the metabolic syndrome in an older population. Although we found a weak association between 24-h urinary cortisol and serum glucose in the total sample (adjusted β = 0.08, p = .02), among depressed persons (N=179) cortisol appeared to be associated more strongly with the obesity-related components of the metabolic syndrome such as waist circumference, triglycerides, and high density lipoprotein cholesterol than with serum glucose.…”
mentioning
confidence: 50%
“…Several community-based studies have investigated the association between MetS and depressive symptoms in the elderly, 6,8,9,11,22,23 and in most this association was confirmed. 6,11,22,23 However, some studies have not detected an association between MetS and depression.…”
Section: Discussionmentioning
confidence: 95%
“…6,11,22,23 However, some studies have not detected an association between MetS and depression. 8,9 This contradiction may be explained at least in part by methodological differences, particularly concerning the assessment of depressive symptoms, definition of depression cases, evaluation of each component of the MetS (e.g., objective laboratorial blood assessments or selfreported risk factors).…”
Section: Discussionmentioning
confidence: 99%
“…[2,[4][5][6][7][8] Depression is also associated with significantly worse outcomes in a number of medical conditions, and depression is an independent risk factor for early mortality (even after accounting for sociodemographic factors, suicide, and biological and behavioral risk factors, such as smoking, alcohol, and physical illness). [9][10][11][12][13] Various explanations for ''accelerated aging'' in depression have been proposed, such as the ''glucocorticoid cascade'' hypothesis [14,15] and ''allostatic load.''…”
mentioning
confidence: 99%